THE IMPACT OF TRAINING AND COMPETENCE ON EMPLOYEE PERFORMANCE - Chairul Hakim; Rulam Ahmadi; Dede Supendi (Jurnal Ekonomi, 2022)
The purpose of the training is to improve employee competence, so that employees who have insufficient abilities or skills can be given training, the aim is to boost employee performance to make it better. So that means training and competence both really influence employee performance. The research method is an activity process in the form of collecting analytical data and providing interpretations related to research objectives. The independent variable is competency and training with the dependent variable being employee performance. Respondents of this study were employees of the Bandung City Development Planning Agency (BAPPEDA). The results of the study showed that training had a positive and significant effect on